Detection of latent tuberculosis infection in household contacts of drug-resistant tuberculosis patients using interferon-gamma release assay: a study at Universitas Indonesia Hospital - Muhammad Faris Indratmo; Diah Handayani; Ardiana Kusumaningrum; Febriana Catur Iswanti; Mohamad Sadikin (Indonesian Society for Biochemistry and Molecular Biology, 2025)
Background: Drug-resistant tuberculosis (DR-TB) poses significant public health challenges in Indonesia. Household contacts of DR-TB patients face elevated risk of Mycobacterium tuberculosis infection, which may remain latent and asymptomatic. Objective: This study aimed to assess the prevalence of latent tuberculosis infection (LTBI) among household contacts of DR-TB patients using interferon-gamma release assay (IGRA). Methods: This cross-sectional study was conducted at Universitas Indonesia Hospital from February to May 2023. Eighteen asymptomatic household contacts from six confirmed DR-TB index cases were enrolled. Participants underwent clinical evaluation, chest radiography, and LTBI screening using the QuantiFERON-TB Gold Plus (QFT-Plus) assay. Results: Among 18 participants (mean age 33.3 years; 55.6% female), 8 (44.4%) tested positive for LTBI, while 10 (55.6%) tested negative. The highest IGRA positivity rates were observed in adolescents aged 12–16 years (66.7%) and young adults aged 17–25 years (60.0%). All participants were clinically asymptomatic with normal chest radiographs. Conclusion: This study demonstrates substantial LTBI prevalence among household contacts of DR-TB patients. The findings underscore the importance of systematic contact tracing, IGRA-based screening, and timely tuberculosis preventive therapy to reduce disease transmission and progression in high-risk populations.